Mortality Following Pediatric Congenital Heart Surgery: An Analysis of the Causes of Death Derived From the National Death Index - Courtney McCracken; Logan G. Spector; Jeremiah Menk; Jessica Knight; Jeffrey M. Vinocur; Amanda S. Thomas; Matthew E. Oster; James D. St. Louis; James H. Moller; Lazaros Kochilas (2018)
Background Prior research has focused on early outcomes after congenital heart surgery, but less is known about later risks. We aimed to determine the late causes of death among children (<21 years of age) surviving their initial congenital heart surgery. Methods and Results This is a retrospective cohort study from the Pediatric Cardiac Care Consortium, a US‐based registry of interventions for congenital heart defects (CHD). Excluding patients with chromosomal anomalies or inadequate identifiers, we matched those surviving their first congenital heart surgery (1982–2003) against the National Death Index through 2014. Causes of death were obtained from the National Death Index to calculate cause‐specific standardized mortality ratios (SMRs). Among 31 132 patients, 2527 deaths (8.1%) occurred over a median follow‐up period of 18 years. Causes of death varied by time after surgery and severity of CHD but, overall, 69.9% of deaths were attributed to the CHD or another cardiovascular disorder, with a SMR for CHD/cardiovascular disorder of 67.7 (95% confidence interval: 64.5–70.8). Adjusted odds ratios revealed increased risk of death from CHD/cardiovascular disorder in females [odds ratio=1.28; 95% confidence interval (1.04–1.58); P =0.018] with leading cardiovascular disorder contributing to death being cardiac arrest (16.8%), heart failure (14.8%), and arrhythmias (9.1%). Other major causes of death included coexisting congenital malformations (4.7%, SMR: 7.0), respiratory diseases (3.6%, SMR: 8.2), infections (3.4%, SMR: 8.2), and neoplasms (2.1%, SMR: 1.9). Conclusions Survivors of congenital heart surgery face long‐term risks of premature mortality mostly related to residual CHD pathology, heart failure, and arrhythmias, but also to other noncardiac conditions. Ongoing monitoring is warranted to identify target factors to address residual morbidities and improve long‐term outcomes.